WHEN THE PORTAL IS NOT ENOUGH: CEREMONIAL TRANSPARENCY AND LEGITIMACY IN THE IMMEDIATE GEOGRAPHIC REGION OF AMARANTE–ÁGUA BRANCA–REGENERAÇÃO (REMUNOM, 2026)
This study analyzes active transparency in the six most populous municipalities of the Immediate Geographic Region of Amarante–Água Branca–Regeneração (Piauí, Brazil), from the perspective of the National Public Transparency Program (PNTP). Adopting a quantitative-explanatory approach, the research employed documentary analysis of municipal transparency portals in 2024 and exploratory Multiple Linear Regression. The results reveal significant heterogeneity: while Amarante achieved a High level of transparency, municipalities such as Palmeirais remained at the Initial level. Statistical analysis indicated that socioeconomic variables (GDP, HDI, population) do not explain performance variations within this sample. It is suggested that higher transparency scores result from strategies aimed at achieving Institutional Legitimacy before society and oversight bodies, whereas lower performance reflects a Ceremonial Adoption (formalism), in which the mere existence of a portal does not ensure usability or real access, thus creating an illusion of transparency. The study concludes that, in small municipalities, political will and administrative capacity outweigh economic factors in determining public transparency. Despite consolidated legislation, the practical implementation of transparency in small municipalities still faces significant obstacles.